Classroom behaviour management strategies in response to problematic behaviours of primary school children with special educational needs: views of special educational needs coordinators. Issue 1 (2nd January 2016) - Nye, Elizabeth; Gardner, Frances; Hansford, Lorraine; Edwards, Vanessa; Hayes, Rachel; Ford, Tamsin
Abstract : Children identified with special educational needs (SEN) and behavioural difficulties present extra challenges to educators and require additional supports in school. This paper presents views from special educational needs coordinators (SENCos) on various strategies used by educators to support children identified with SEN and problematic behaviours. The data were collected from telephone interviews with six SENCos from the UK's South West Peninsula. The SENCos were invited to participate because their school was participating in a cluster-randomised trial of a teacher classroom management course (Incredible Years). Using thematic analysis to analyse the data, this paper illustrates strategies deemed by SENCos to be successful in the support of children identified with SEN. The management strategies generated by participating SENCos were then mapped onto those taught as part of the classroom management course for comparison. Findings indicate that strategies from the training programme appear to be appropriate for children identified with both SEN and behavioural difficulties.